Behavior and food consumption pattern of the population exposed in 1949-1962 to fallout from Semipalatinsk nuclear test site in Kazakhstan - Drozdovitch, Vladimir; Schonfeld, Sara; Akimzhanov, Kuat; Aldyngurov, Daulet; Land, Charles E; Luckyanov, Nickolas; Mabuchi, Kiyohiko; Potischman, Nancy; Schwerin, Michael J; Semenova, Yulia; Tokaeva, Alma; Zhumadilov, Zhaxybay; et al. (Radiation and environmental biophysics, 2011)
The relationship between radiation exposure from nuclear weapons testing fallout and thyroid disease in a group of 2,994 subjects has been the subject of study by the US National Cancer Institute. In that study, radiation doses to the thyroid were estimated for residents of villages in Kazakhstan possibly exposed to deposition of radioactive fallout from nuclear testing conducted by the Soviet Union at the Semipalatinsk Nuclear Test Site in Kazakhstan between 1949 and 1962. The study subjects included individuals of both Kazakh and Russian origin who were exposed during childhood and adolescence. An initial dose reconstruction used for the risk analysis of Land et al. (Radiat Res 169:373-383, 2008) was based on individual information collected from basic questionnaires administered to the study population in 1998. However, because data on several key questions for accurately estimating doses were not obtained from the 1998 questionnaires, it was decided to conduct a second data collection campaign in 2007. Due to the many years elapsed since exposure, a well-developed strategy was necessary to encourage accurate memory recall. In our recent study, a focus group interview data collection methodology was used to collect historical behavioral and food consumption data. The data collection in 2007 involved interviews conducted within four-eight-person focus groups (three groups of women and one group of men) in each of four exposed villages where thyroid disease screening was conducted in 1998. Population-based data on relevant childhood behaviors including time spent in- and outdoors and consumption rates of milk and other dairy products were collected from women's groups. The data were collected for five age groups of children and adolescents ranging from less than 1 year of age to 21 years of age. Dairy products considered included fresh milk and other products from cows, goats, mares, and sheep. Men's focus group interviews pertained to construction materials of houses and schools, and animal grazing patterns and feeding practices. The response data collected are useful for improving estimates of thyroid radiation dose estimates for the subjects of an ongoing epidemiological study.